Issues of Development of Pedagogical Education in Ecclesiastical Academies in the Heritage of Teachers of Educational Institutions of the Orthodox Church (Beginning of the 19th – 60s of the 19th Century) - Tetiana Tverdokhlib (Pedagogical Discourse, 2017)
The coverage of issues of the development of pedagogical education in the domestic higher ecclesiastical school in the works of teachers of educational institutions of the Orthodox Church at the beginning of the nineteenth century - in the 60’s of the nineteenth century has been considered. Pedagogical education in the study has been determined as a system of training pedagogical and scientific and pedagogical staff for educational institutions of all types and as a professional training of future priests for the religious and moral upbringing of the flock.It has been found that published works of teachers of ecclesiastical educational institutions in the first half of the nineteenth century were rarity. They were characterized by thematic scantiness and did not cover the problems of pedagogical education. The ideas on teaching pedagogy in the ecclesiastical academies, presented in unpublished projects of the rectors of the Kiev Theological Academy, Bishop Inokentii Chyhyrynskyi (Borysov) and Archimandrite Dymytrii (Muretov), ​​have been analyzed. It has been proved that Bishop Inokentii only outlined the main shortcomings of higher theological education, which required correction, and expressed some general considerations about the ways of its reformation, the need to study pedagogy in particular. It has been determined that in comparison with his project, the project of Archimandrite Dymytrii differed in greater detail, completeness and practical orientation. It provided for specific ideas on the organizational aspect of introducing pedagogy into curriculum, and determined its content (theory of education, general and special parts of the «science of teaching», the latter covered the specifics of teaching at all levels of the system of ecclesiastical education). Particularly Archimandrite Dymytrii dwelt on the issue of conducting pedagogical practice, and drew attention to the teaching and methodological support for the study of a new subject.Basing on the analysis of primary sources and historical and pedagogical literature, the opinions of other teachers of the Kyiv, Kazan, Moscow and St. Petersburg theological academies have been revealed. Their views related to teaching in academies not only pedagogy, but also pedagogically oriented disciplines. Thoughts of teachers were presented on the pages of the national ecclesiastical periodicals in the 1860’s. It has been concluded that these ideas mainly concerned changes in the content, forms, methods, organization of the teaching of pastoral theology, homiletics and pedagogy.